Perkembangan Pendidikan Islam Masa Awal Di Sumatera Barat, Lembaga dan Tokohnya - Zikriadi; Bahaking Rama; Muhammad Rusdi Rasyid (PIJAR: Jurnal Pendidikan dan Pengajaran, 2023)
This study discusses the development of Islamic Education in West Sumatra, both from the perspective of institutions and figures. It is important to review this again because there is too much scattered literature, thus requiring this paper to remap from an institutional perspective and Islamic Education figures in West Sumatra. This research is included in the literature review with the stages of analysis in the form of data reduction, data exposure, and conclusions/verification. The results show that the role of Islamic Education figures in the early days greatly influenced the development of Islamic Education in West Sumatra, the Burhanuddin Ulakan figure made Surau the forerunner of Islamic learning facilities. After that, the existence of Ahmad Khatib gave birth to many scholars in Indonesia, especially in West Sumatra. From there, figures in the development of Islamic Education who contrasted established Educational Institutions, such as Abdullah Ahmad founded the Adabiyah School, Zainuddin Labay el-Yunusi founded the Diniyah School, Rahmah el-Yunusi founded Madrasah Diniyah Putri, and Abdul Karim Amrullah founded Sumatra Thuwailib.